Developing a framework to facilitate a culture for continuous improvement within higher education institutions: the case of Saudi Arabia. - Alotaibi, Mohammed (Cranfield University, 2019)
Continuous Improvement in HEIs is becoming increasingly an important part of the HEIs strategic management. Major changes in the higher education sector over the last two decades have exerted pressure on the ability of HEI systems to sustain quality, meet increasing demands for accountability, and demonstrate their economic and social role. The drive for quality management and quality assurance has manifested in the increase in accreditation and quality audits required of HEIs by government bodies and external entities. Saudi Arabia higher education system is not exceptional in this regard. Therefore, this explanatory and interpretive study adopted a qualitative grounded theory approach, which, aims to establish how organisational culture can be leveraged to support continuous improvement in Saudi Arabia’s HEIs. It has used a number different data gathering instruments: including, face-to-face interviews, focus groups and survey. It also, identifies a number of themes that influence CI implementation in Saudi HEIs, and develop a framework of interventions that will help to leverage the organisation cultures of Saudi Arabia HEIs to facilitate continuous improvement. Recommendations for further study included more focused studies on the OC of Saudi based private universities and their current CI practices.
Keywords: Organisational cultures; continuous improvement; higher education institutions; grounded theory; strategic management; quality; accountability